2014
DOI: 10.7888/juoeh.36.159
|View full text |Cite
|
Sign up to set email alerts
|

Towards Prenatal Biomonitoring in Eastern Nigeria: Assessing Lead Levels and Anthropometric Parameters of Newborns

Abstract: : The purpose of this study is to measure maternal blood lead level (BLL) and cord BLL in Nigeria and to compare Nigerian data with other data. We investigated the association among maternal and cord BLLs, and some anthropometric parameters of their babies. BLL was measured in the umbilical and maternal blood samples (using inductively coupled plasma / mass spectrometry (ICP-MS)) of 119 women who delivered at three different hospitals in Nnewi, South Eastern Nigeria. Anthropometric variables of the babies (hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 62 publications
0
16
0
Order By: Relevance
“…Benin republic, Botswana, Ethiopia, Kenya, Senegal, and Zambia had one study each. Ten of the studies (30, 45–47, 49–55) were on pregnant/delivering women, 2 studies (26, 57) were on mothers of infants, 1 study (56) was generally on women of childbearing age and one of the studies was on non-pregnant women of childbearing age, with occupational exposure to lead (48). Seven of the studies (30, 45, 46, 49, 51–53, 55) did not report the sources of lead exposure in the study population.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Benin republic, Botswana, Ethiopia, Kenya, Senegal, and Zambia had one study each. Ten of the studies (30, 45–47, 49–55) were on pregnant/delivering women, 2 studies (26, 57) were on mothers of infants, 1 study (56) was generally on women of childbearing age and one of the studies was on non-pregnant women of childbearing age, with occupational exposure to lead (48). Seven of the studies (30, 45, 46, 49, 51–53, 55) did not report the sources of lead exposure in the study population.…”
Section: Resultsmentioning
confidence: 99%
“…Ten of the studies (30, 45–47, 49–55) were on pregnant/delivering women, 2 studies (26, 57) were on mothers of infants, 1 study (56) was generally on women of childbearing age and one of the studies was on non-pregnant women of childbearing age, with occupational exposure to lead (48). Seven of the studies (30, 45, 46, 49, 51–53, 55) did not report the sources of lead exposure in the study population. Eleven of the studies were hospital-based (30, 45–47, 49–52, 54, 55, 57), subjects for three of the studies (26, 53, 56) were recruited through community mobilization campaigns while one study was field-based mouth-to-mouth campaign (48).…”
Section: Resultsmentioning
confidence: 99%
“…There is a paucity of data from other African countries but indications are that prenatal exposure to Pb is fairly common. A recent study from Eastern Nigeria has reported paired maternal and cord blood Pb levels of 6.19 μg/dL and 4.75 μg/dL, respectively [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increased umbilical cord blood lead levels were associated with decreased birth weight, 37 , 40 decreased birth length, 19 , 40 intrauterine growth restriction, 20 lower gestational age, 21 decreased crown-rump length, 38 and increased risk of preterm labor. 29 Whereas others found no association between birth weight, 31 , 33 gestational age, 31 head circumference, 33 crown-heel length, 33 and elevated umbilical cord blood levels.…”
Section: Anthropometric Consequencesmentioning
confidence: 96%
“…21 The samples of infant-mother dyads were from a myriad of countries including Brazil, 40 Mexico, 16 Iran, 20 , 29 Saudi Arabia, 36 , 39 India, 21 , 30 Tanzania, 31 Poland, 17 Spain, 32 Kuwait, 33 Belgium, 34 China, 19 Argentina, 35 South Korea, 37 and South Eastern Nigeria. 38 Five of the studies 16,17,29,36,37 utilized longitudinal designs to evaluate infant anthropometric growth or developmental outcomes in relationship to maternal lead levels changes throughout pregnancy or to examine cognitive outcomes in infants exposure to Pb 2 + based on umbilical cord blood level samples. For context, when much of the data were collected, the Centers for Disease Control and Prevention (CDC) recommendation was Pb 2 + level 10 μ g/dL or less; however, a Pb 2 + level of 5 μ g/dL or more is considered a level 418 Allen of concern.…”
Section: Summary Of Evidencementioning
confidence: 99%